Clinical and physiological characteristics of organs and mouth tissues of the residents in industrial of Yakutia (Эндодонтия Today)
Analysis of the results of complex clinical and epidemiological studies conducted in industrial areas of the Republic of Sakha (Yakutia) determines the high prevalence of dental diseases. The evaluation of laboratory data suggests the presence of certain changes in composition and properties of oral fluid among population that are associated with an increase in viscosity and a decrease in salivary flow rate with a predominance of the second and third types of oral fluid microcrystallization. At the same time these changes of biophysical properties of the oral fluid accompanied by low calcium content, decrease in activity of alkaline phosphatase and its remineralizing function among different age groups. Residents of Tompo, Oimyakon, Niurba, Anabar areas with developed mining industry revealed a high level of needs and insufficient dental care. The health system is determined by insufficiency of some experts of dental profile, and the absence of any preventive measures. Identified changes in composition and properties of the oral fluid can be provided as biological risk factors of formation and development of pathological processes of organs and mouth tissues, and they should be considered in the organization of therapeutic and preventive care to the population of industrial areas of the North.